Obstacles of e-learning among mathematics teachers in basic education schools in the Governorate of North Al Batinah in the Sultanate of Oman and its relationship to some demographic variables - Al-Kamashki, Mohammed Ahmed Abdullah; Yusuf, Muhammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the obstacles of e-learning among mathematics teachers in basic education schools in the Governorate of North Al Batinah in the Sultanate of Oman. The researcher followed the descriptive method to achieve the study's aims. The tool of the study was a questionnaire consist of (29) sentences. The questionnaires were distributed to a random sample of (216) males and females' teachers. The results of the study showed that the obstacles to e-learning among teachers came to a medium degree, and the total average of the degrees was (3.61), With a percentage of (72%). The results also indicated that there were statistically significant differences due to gender in favor of females, and the results showed the presence of statistically significant differences due to years of experience, and in favor of more than 10 years. According to the results, the study recommends improving the infrastructure and technical and technological equipment in schools, working to increase training courses for teachers on the use of e-learning, providing experts in the use of e-learning and providing technical support for technical issues.
Keywords: Obstacles of e-learning; mathematics teachers; basic education; Al Batinah North